A geostatistical approach for predicting the top producing formation in oil fields - Abdideh, Mohammad; Abyat, Majed (Geodesy and Cartography, 2012)
Drilling engineer’s understanding of the subsurface conditions of oil-rich regions in Iran is based on experience and through quantitative assessment of these valuable data. The usage of geostatistical methods converts the qualitative experience to quantitative and provides the way for better result. In Iranian oil fields, during the drilling operation Asmari formation is of great importance because most of oil reservoirs are located in this formation. In this study, 53 wells in the field were randomly selected, and after studying and reviewing the drilling and geological reports, 40 wells were selected for inclusion in the model. After analysis of the information, a model which predicts the top of Producing Formation accurately was presented.